2016
DOI: 10.1016/j.gie.2016.01.068
|View full text |Cite
|
Sign up to set email alerts
|

EUS Needle Identification Comparison and Evaluation study (with videos)

Abstract: Background and Aims Endoscopic ultrasound (EUS)-guided fine-needle aspiration (FNA) or biopsy is widely practiced. Optimal sonographic visualization of the needle is critical for image guided interventions. There are several commercially available needles but no bench-top testing and direct comparison of these needles to reveal their inherent echogenicity. The aims are to provide bench-top data that can be used to guide clinical applications and to promote future device research and development. Methods Desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 18 publications
(17 reference statements)
0
24
0
Order By: Relevance
“…The overall complication rate in our study was 2.7%, which is comparable to the reported complication rates for EUS-FNA between 1 and 2.5%. 20 In our experience, there was no significant difference in sonographic echogenicity between the three needles. A recent study by Tang, et al compared eight of the most commonly used needles including our three needles.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The overall complication rate in our study was 2.7%, which is comparable to the reported complication rates for EUS-FNA between 1 and 2.5%. 20 In our experience, there was no significant difference in sonographic echogenicity between the three needles. A recent study by Tang, et al compared eight of the most commonly used needles including our three needles.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, needles with clear echogenic features are ranked better than others amongst gastroenterologists. 20 The study did not look into the diagnostic accuracy or adequate sampling between needles. 20 In our experience, there was no significant difference in sonographic echogenicity between the three needles.…”
Section: Discussionmentioning
confidence: 99%
“…108 To facilitate localization using ultrasound, needles, particularly those used for endoscopy, may have surface modifications such as polymer coating or etching to enhance echogenicity. 109 Recently, ultrasound vibration of the needle has been used experimentally to enhance needle visibility. 110 Biopsy Device Form Factor, Maintenance, Reliability Form factor is the term used to specify the size, configuration, physical arrangement, and specifications of device hardware.…”
Section: Biopsy Needle Design and Gaugementioning
confidence: 99%
“…FNA needles have different echogenicity . In a multicenter study evaluating 10 different EUS needles, the polymeric‐coated needle showed the highest echogenicity …”
Section: Interventional Eus: New Tools New (And Old) Applicationsmentioning
confidence: 99%
“…[49][50][51] In a multicenter study evaluating 10 different EUS needles, the polymeric-coated needle showed the highest echogenicity. 52 Consistent tissue core acquisition with EUS-guided biopsy has recently been achieved through the development of new side-and end-cutting EUS needles, with different mechanisms, calibers and design. 53 The Quick-Core needle (Cook Medical, Bloomington, IN, USA) is a 19-G-Tru-Cut biopsy needle; 54 the 19-and 22-G ProCore needles have a lateral opening with reverse-bevel technology.…”
Section: Fusion Imagingmentioning
confidence: 99%